INTEGRASI LINGUISTIK TEORETIS DAN EDU-LINGUISTIK DALAM PENGAJARAN BAHASA ARAB DI ERA DIGITAL (Kajian Konseptual Studi Pustaka): Integrasi Paradigma Linguistik Teoretis dan Edu-Linguistik dalam Pembelajaran Bahasa Arab Kontemporer - Dadeng Irman Fauzi; Munir Ashadi; Wati; Iis Susiawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the integrative relationship between theoretical linguistics and edu-linguistics in the context of modern Arabic language education. Using a qualitative approach with a library research method, this study reviews academic literature from various subfields of linguistics (phonology, morphology, syntax, semantics, and pragmatics) as well as recent research on technology-based Arabic language teaching. The findings indicate that linguistic theory serves as a crucial scientific foundation for understanding the structure, meaning, and function of the Arabic language. The integration of linguistics with pedagogical aspects results in a more comprehensive and contextual edu-linguistic approach by combining theoretical, methodological, and Islamic educational values. In the digital era, this integration is strengthened through the use of learning technologies such as e-learning platforms, linguistic analysis software, and speech-recognition applications that enhance Arabic language skills interactively and independently. Thus, edu-linguistics in modern times functions not only as a bridge between theory and practice but also as a new paradigm for curriculum development, teaching methods, and value-based assessment.